On the Way to Big Data Applications in Industrial Computed Tomography - Ditter, Alexander; Fey, Dietmar; Schön, Tobias; Steven, Oeckl (Proceedings of BigData Congress 2014, 2014)
Computed Tomography (CT) has been around, especially in the medical field, for more than 20 years. Although, the mathematical foundations for CT were known more than a century ago, technical limitations delayed its practical application for more than 70 years. Today, we can build CT systems large enough to scan an entire car, yet, for the processing of the resulting data we are facing a 'Big (sensor) Data Problem'. We currently do not have suitable methods and tools and cannot handle the large amount of data with conventional state-of-the-art techniques. As industrial CT became more and more prevalent over the last few years, especially due its unique features in the field of non destructive testing, we are proposing and evaluating the use of new methods, work flows and technologies, such as Cloud Computing, in order to provide suitable solutions for handling the steadily growing amount of data and its efficient processin
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD3.onthew
Keywords: compression; industrial computed tomography; nondestructive testing; sensor data; streaming